Recently excavated Iron Age burials from the Western Isles. Issue 1 (March 2018) - Cook, Martin
Abstract : Between 2004 and 2008, AOC Archaeology Group undertook the excavation of four separate Iron Age burials. These remains had been exposed by coastal erosion, and were excavated under the terms of the Historic Scotland Call-Off Contract for Human Remains; the four inhumations were fully excavated and radiocarbon dated. The excavations provide new evidence for Iron Age burial practice in the Western Isles and, more generally, Scotland. The examples discussed here from Scarista, Vallay, Griminish and Drimsdale were all unaccompanied burials, which by the position of the body in the grave and/or the grave setting, may have, in the past, been interpreted as possible Bronze Age or Early Historic graves in the absence of direct dates obtained from the human skeletal remains. These recent discoveries emphasise the necessity for the application of radiocarbon techniques (in the common absence of grave goods) to classify burials chronologically.